Análise do conteúdo de marketing nos cursos de administração no Brasil bem avaliados pela CAPES - Santos Junior, Valmir de Santana (2022)
This paper presents a comparative study of the similarities and differences between the contents presented in the Stricto Sensu Post-Graduation program in the area of administration in Brazil, from the perspective of the importance of the marketing discipline in educational institutions. The academic masters' courses that were well evaluated according to the criteria of CAPES (Coordination for the Improvement of Higher Education Personnel) were selected. For this research the CAPES database was updated until the year 2019. The methodology used in this work is qualitative research employing the content analysis techniques proposed by Bardin (1977). This research aims to present the differences and similarities between the marketing contents of the courses, seeking to contribute with new programs in the construction of their contents and also with CAPES in the sense of the search for a reflection regarding the evaluation method in force